Workers describe the effect of the workers' compensation process on their health: A Québec study - Lippel, Katherine (Université d'Ottawa | University of Ottawa, 2007)
This article reports on a Canadian qualitative study designed to examine the workers' experience of the workers' compensation process and to look at the effects of the process on the physical and mental health of claimants. Eighty five in depth individual interviews of injured workers in Québec and six group interviews with workers and worker advocates from Québec, Ontario and British Columbia were analysed to determine the positive and negative impact on claimant health of various steps of the workers' compensation process and of behaviours of significant actors in that process. While superior access to health care and access to economic support both contributed to claimant well-being, various facets of the process undermined the mental health of workers, and in some cases, also had a negative impact on physical health. Primary characteristics of the process that influenced outcomes included stigmatization of injured workers and the significant power imbalance between the claimants and the other actors in the system; the effect of both these mechanisms was tempered by social support. The article describes how caseworkers, physicians, appeal tribunals, employers and compensation boards contribute to the positive or negative impacts on worker health and concludes with recommendations designed to promote the therapeutic aspects of workers' compensation and to curtail those facets that are harmful to worker health. It also has implications for researchers who wish to consider the role of lawyers or compensation in the development or prevention of disability Written from both a legal and public health perspective, this paper has two primary objectives: first, to better understand the potential and limits of the current legislative framework for the protection of the mental health of workers and second, to describe how scientific knowledge related to high risk situations for the mental health of workers might inform interventions by inspectors for the protection of workers’ mental health.